Periode Akhir Revolusi Fisik di Bali, 1946-1949 - Arta, Ketut Sedana; Yasa, I Wayan Putra; Pageh, I Made; Pardi, I Wayan (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This research aims to investigate Puputan Margarana and its impact on the physical revolution in Bali, both from a military and psychological perspective, and then to gain a clearer understanding of the tactics and strategies of resistance in Bali following the Puputan Margarana. This study employs historical methods encompassing heuristics, criticism, interpretation, and historiography. The research findings indicate that the impact of Puputan Margarana resulted in psychological turmoil for the fighters in the Buleleng region, leading to sadness and a profound sense of loss due to the fall of Ngurah Rai and his staff. The post-Puputan Margarana physical revolution in Bali witnessed the reorganization of MBU-DPRI and the emergence of MBI, along with various persuasive actions to implement the minimum Banyuning program, the infiltration of DPRI's influence into government organs, and acts of violence against those openly supportive of NICA. With the achievement of the Renville Agreement in 1948, the shift in resistance in Buleleng came to be known as the "penurunan" (covert withdrawal) and "penyerahan" (official surrender), as orchestrated by Wijakusuma and the core leaders of MBU-DPRI.